Evaluation of the safety and the reliability of day case mini-PCNL in treatment of renal stones 1 to 2 cm - D. Mostafa; T. M. El-zayat; M. A. Omer; M. S. Salem (Амбулаторная хирургия)
Introduction. The capacity to execute mini percutaneous nephrolithotomy (PCNL) as a day case procedure in the treatment on renal stones measuring between one and two centimetres is being assessed in this study. Mini-PCNL has been employed more and more in the treatment on renal stones with favourable results in terms on stone clearance and low morbidities.Aim. To find a reliable replacement for E.S.W.L. and R.I.R.S in treating small renal stones that is safe, efficient, and reliable with the shortest post-operative stay period.Materials and methods. Seventy patients underwent surgery for kidney stones that ranged in size from 1 to 2 cm and had densities greater than 1000 H.U. They were split into two groups: group B received mini-PCNL and group A received regular PCNL. Both procedures were carried out while the patients was in the prone position. In group A, we fragmented the material with an electrohydraulic lithotripter and removed the resulting fragments using forceps. In contrast, group B employed a 30 w Quanta Holmium laser in dusting mode (0.5 j and 15 Hz) with 550 um laser fibre and relied on our exit plan for the double-J stent implantation, which avoided the necessity for a nephrostomy tube.Results. Operation duration was significantly longer in mini-PCNL group (p < 0.001). Intraoperative extravasation and its severity were non-significantly less frequent in mini-PCNL group (p > 0.05). All patients operated with mini-PCNL underwent double j stent, while the other group included only two patients who necessitated double J insertion insertion, and the remaining 33 patients depended on the insertion on a nephrostomy tube together with a ureteric catheter.Conclusion: Mini-PCNL is a dependable day case method that is safe for treating tiny kidney stones. Larger sample size studies could be required to confirm mini-PCNL as a day case technique.